ON EUROPEAN IDENTITY:AN INTERDEPENDENCE OF ITS AXIOLOGICAL DIMENSION AND SUPRANATIONAL NATURE (Вісник: Міжнародні відносини, 2022)
The article deals with the current trends and features of the axiological (i.e., values) aspect of European identity as an integral part of European integration and geopolitics. It shows an interconnexion between the notions of 'values' and 'identity' from the standpoint of geopolitics; describes the evolution of the axiology of European identity, in particular in terms of its compatibility with national identities; and features its evolution at the present stage, with both foreign and domestic political factors taken into account. Given the dynamic nature of values, it is concluded that an understanding of the values component of (geo)political identity frames the peculiarities of current European integration.
Keywords: European identity, European integration, values, axiology.